Bioactive starch-based scaffolds and human adipose stem cells are a good combination for bone tissue engineering - Rodrigues, A. I. (2012)
Silicon is known to have an influence on calcium phosphate deposition and on the differentiation of bone precursor cells. This study explores the effect of the incorporation of silanol (Si–OH) groups into poly- meric scaffolds on the osteogenic differentiation of human adipose stem cells (hASC) cultured under dynamic and static conditions. A blend of corn starch with polycaprolactone (30/70 wt.%, SPCL) was used to produce three-dimensional fibre meshes scaffolds by the wet-spinning technique, and a calcium sili- cate solution was used as a non-solvent to develop an in situ functionalization with Si–OH groups. In vitro assessment, using hASC, of functionalized and non-functionalized scaffolds was evaluated in either a- MEM or osteogenic medium under static and dynamic conditions (provided by a flow perfusion bioreac- tor). The functionalized materials, SPCL–Si, exhibit the capacity to sustain cell proliferation and induce their differentiation into the osteogenic lineage. The formation of mineralization nodules was observed in cells cultured on the SPCL–Si materials. Culturing under dynamic conditions using a flow perfusion bioreactor was shown to enhance the hASC proliferation and differentiation and a better distribution of cells within the material. The present work demonstrates the potential of these functionalized mate- rials for future applications in bone tissue engineering. Additionally, these results highlight the simplicity, economic and reliable production process of those materials.